Finaritra! A splendid new leaf-tailed gecko (Uroplatus) species from Marojejy National Park in north-eastern Madagascar - Ratsoavina, Fanomezana Mihaja; Raselimanana, Achille P.; Scherz, Mark D.; Rakotoarison, Andolalao; Razafindraibe, Jary H.; Glaw, Frank; Vences, Miguel (Zootaxa, 2019)
The Marojejy Massif in northern Madagascar is a constant source of herpetological surprises. Herein we describe a new species of leaf-mimicking leaf-tailed gecko, Uroplatus finaritra sp. nov., based on morphological and molecular phylogenetic evidence. This new species inhabits the rainforests of Marojejy National Park at low elevations and is morphologically similar to Uroplatus phantasticus, but differs by having a larger body size, relatively shorter tail, and dark-red pigmentation of the oral mucosa. Molecular data reveals a distance of 14.0–14.7% in the 16S rRNA gene to U. phantasticus, and haplotype sharing in the c-mos nuclear gene only with species of much shorter tails (i.e., with U. kelirambo and two undescribed candidate species). Similar to other members of the leaf-mimicking Uroplatus species in northern Madagascar, Uroplatus finaritra sp. nov. likely has a small geographic distribution, and is currently known only from the lowland rainforests of Marojejy. We discuss the value of the buccal mucosa colouration and tail dimensions of Uroplatus as taxonomic characters, and the potential drivers of their evolution. In order to reduce the risk of international trade under incorrect species names we suggest that exported CITES species should be obligatorily accompanied by information about their precide geographic origin within Madagascar.